2021
DOI: 10.3390/cancers13133094
|View full text |Cite
|
Sign up to set email alerts
|

How Researchers, Clinicians and Patient Advocates Can Accelerate Lobular Breast Cancer Research

Abstract: Breast cancer research and therapies have significantly advanced in recent years. However, Invasive Lobular Carcinoma (ILC), the second most common histological type of breast cancer and the sixth most frequently diagnosed cancer of women, has not always benefited from critical analysis, missing opportunities to better understand this important subtype. Recent progress understanding the biological and behavioral differences of ILC demonstrates that it is a unique subtype of breast cancer which can respond diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Furthermore, more insights arise regarding dormancy of ILC cells, which might reveal new treatment options in the future. Clinical trials focusing on ILC are emerging and collaborative efforts between clinicians, researchers and patient advocates are increasing, 205 which hopefully enables more prospective clinical and translational research to provide the optimal treatment strategies for patients with ILC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more insights arise regarding dormancy of ILC cells, which might reveal new treatment options in the future. Clinical trials focusing on ILC are emerging and collaborative efforts between clinicians, researchers and patient advocates are increasing, 205 which hopefully enables more prospective clinical and translational research to provide the optimal treatment strategies for patients with ILC.…”
Section: Discussionmentioning
confidence: 99%
“… 13 The dominance of breast cancer research in the field of women’s health research appears to be attributable to several factors: public awareness of its higher incidence, the development of innovative anti-cancer drugs, a well-established research network, diverse funding resources, good accessibility to biomaterials, and the active participation of patients in clinical trials. 11 30 31 32 33 Given the high burden of musculoskeletal disorders, diabetes, urogenital disorders, and blood and endocrine diseases in Korean women, more attention is required to diverse health issues across the life course of women. 34 The lack of diversity in women’s health studies was also illustrated shown by the current result of text analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of rigorous standards for reporting on PDX models hampered researchers' finding relevant PDX models and associated data, including ILC PDXs [170]. The European Lobular Breast Cancer Consortium (ELBCC) aims to bridge this gap in translational ILC research and provide an unprecedented clinical impact due to the streamlining of the "from bench-to-bedside" principle to enable uniform diagnosis and tailored treatment for patients with ILC [209]. To this aim LOBSTERPOT, a COST-funded (European Cooperation in Science and Technology) action initiated by the ELBBC, proposes to combine discovery science, translational studies, and clinical implementation to improve the understanding, diagnosis, treatment, and prognosis of women suffering from ILC; https://www.cost.eu/actions/CA19138.…”
Section: Ilc Initiatives and Repositories Of Ilc Modelsmentioning
confidence: 99%